Complete Genome Sequence of Enterobacter cloacae 704SK10, an OXA-48-Encoding Wastewater Isolate - Marti, Roger (Genome Announc, 2017)
Here we present the complete genome sequence of Enterobacter cloacae 704SK10, a Swiss wastewater isolate encoding an OXA-48 carbapenemase. Assembly resulted in closed sequences of the 4,876,946-bp chromosome, a 111,184-bp IncF plasmid, and an OXA-48-encoding IncL plasmid (63,458 bp) nearly identical to the previously described plasmid pOXA-48.